PENGEMBANGAN MEDIA PUZZLE BERBASIS MAKE A MATCH PEMBELAJARAN BERBAGAI PEKERJAAN KELAS IV SEKOLAH DASAR - Revina Mayang Sari; Nugraha Permana Putra (PGSD Universitas Muhammadiyah Cirebon, 2022)
This research is motivated by learning in the classroom which still uses the lecture method during the learning process that takes place in the classroom and has not used learning media because of the limitations of learning media in schools. This study aims to develop a Puzzle learning media that is suitable for use for students in grade IV Elementary School 2 Karangmulya Plumbon. This type of research is research and development or what we usually call R&D (Research and Development) by following the procedures from Borg and Gall. The research stages include 1) information gathering 2) media product planning 3) media product development and 4) material expert validation, media. The results of this puzzle learning media research are adjusted to the formulation of the problem as follows 1). The development of puzzle media that is specifically planned for 4 sub-theme 2 themes for various social studies learning work using the Brog and Gall research approach with 4 stages. 2). The validity of the puzzle media which was assessed based on the validity test carried out by the validator, with the average obtained from the validation results of the three material experts were 100%, 100%, and 97.9% included in the